Contribution of Saharan Dust to Ion Deposition Loads of High Alpine Snow Packs in Austria (1987–2017) - Greilinger, Marion; Schauer, Gerhard; Baumann-Stanzer, Kathrin; Skomorowski, Paul; Schöner, Wolfgang; Kasper-Giebl, Anne (Frontiers in Earth Science, 2018)
We investigate the influence of Saharan dust on the chemical composition and deposition loads of a 31-year long snow chemistry data set (1987–2017) of high alpine snow packs situated close to the Sonnblick Observatory, a global GAW (Global Atmospheric Watch) station, in the National Park Hohe Tauern in the Austrian Alps. Based on the snow pack of the winter accumulation period 2015/2016, when two Saharan dust events were visible by a reddish color of the snow, we define a pH > 5.6 together with a Ca2+ concentration > 10 μeq/l as thresholds to identify Saharan dust affected snow layers. This criterion is checked with an intercomparison with trajectories and on-line aerosol data determined at the Sonnblick Observatory. This check was extended to the accumulation periods 2014/2015 and 2016/2017 before the whole time series is investigated regarding the contribution of Saharan dust to ion deposition loads. Especially Mg2+, Ca2+, and H+ depositions are strongly affected by Saharan dust input causing, as average values across the 30 years period, increased Mg2+ (25%) and Ca2+ (35%) contributions of affected snow layers, while the contribution to the snow water equivalent was only 11%. For H+ Saharan dust affected snow layers show a much lower contribution (2%) while the contribution of other ions is well comparable to the deposition amount expected according to the snow water equivalent of affected snow layers. The pH range of Saharan dust affected snow layers covers 5.58–7.17, while the median value of all samples is 5.40. The long term trends of ion deposition are not affected by the deposition of Saharan dust.